2022
DOI: 10.3390/en15176179
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Thermally Activated Building Systems (TABS) as an Alternative for Improving the Indoor Environment of Buildings

Abstract: Among the alternatives for improving the thermal comfort conditions inside buildings are the thermally activated building systems (TABS). They are embedded in different building components to improve the indoor air temperature. In this work, a review and analysis of the state of the art of TABS was carried out to identify their potential to improve thermal comfort conditions and provide energy savings. Furthermore, this study presents the gaps identified in the literature so that researchers can develop future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…According to the data collected, higher electrical energy consumption is associated with using air conditioning to cool the spaces that patients and staff frequent to a greater extent. These results are consistent with the literature, where it is reported that air conditioning equipment represents about 66% of electricity consumption in regions with hot-subhumid or similar climates [23]. In facilities for the care of patients, health, or other small-sized related matters, it has been verified that the energy consumption for air conditioning is around 60% [24].…”
Section: Building Information: Outpatient Medical Centersupporting
confidence: 91%
“…According to the data collected, higher electrical energy consumption is associated with using air conditioning to cool the spaces that patients and staff frequent to a greater extent. These results are consistent with the literature, where it is reported that air conditioning equipment represents about 66% of electricity consumption in regions with hot-subhumid or similar climates [23]. In facilities for the care of patients, health, or other small-sized related matters, it has been verified that the energy consumption for air conditioning is around 60% [24].…”
Section: Building Information: Outpatient Medical Centersupporting
confidence: 91%
“…Pipe-embedded building envelopes coupled with cooling/heating source systems have gained increasing attention in recent years as a way to improve the energy efficiency and thermal comfort of buildings. Pipe-embedded building envelopes are also known as thermally active building system (TABS) [14,25], concrete core slab, active tuning building wall [15], etc. These systems involve the integration of pipes into the building envelope, typically in the form of walls [18,19], floors [26,27], or ceilings [28][29][30], which are used to distribute a cooling or heating fluid to the interior space.…”
Section: Introductionmentioning
confidence: 99%
“…During periods of high thermal load, heat is transferred through the floor and ceiling and stored in concrete; it can then be removed by water flowing in pipes when the occupants are absent [6]. Spreading the removal of heat over a longer period results in lower peak power requirements for cooling systems, which can lead to energy savings up to 50% [7].…”
Section: Introductionmentioning
confidence: 99%